Phenotypes of Chronic Hepatitis B in Children From a Large North American Cohort. Issue 5 (November 2019) - Schwarz, Kathleen B.; Lombardero, Manuel; Di Bisceglie, Adrian M.; Murray, Karen F.; Rosenthal, Philip; Ling, Simon C.; Cloonan, Yona Keich; Rodriguez-Baez, Norberto; Schwarzenberg, Sarah Jane; Hoofnagle, Jay H.; Teckman, Jeffrey
ABSTRACT: Objective: The aim of the study was to define chronic HBV phenotypes in a large, cohort of United States and Canadian children utilizing recently published population-based upper limit of normal alanine aminotransferase levels (ULN ALT), compared with local laboratory ULN; identify relationships with host and viral factors. Background: Chronic hepatitis B virus (HBV) infection has been characterized by phases or phenotypes, possibly associated with prognosis and indications for therapy. Methods: Baseline enrollment data of children in the Hepatitis B Research Network were examined. Phenotype definitions were inactive carrier: HBeAg-negative with low HBV DNA and normal ALT levels; immune-tolerant: HBeAg-positive with high HBV DNA but normal ALT levels; or chronic hepatitis B: HBeAg-positive or -negative with high HBV DNA and abnormal ALT levels. Results: Three hundred seventy-one participants were analyzed of whom 274 were HBeAg-positive (74%). Younger participants were more likely be HBeAg-positive with higher HBV DNA levels. If local laboratory ULN ALT levels were used, 35% were assigned the immune tolerant phenotype, but if updated ULN were applied, only 12% could be so defined, and the remaining 82% would be considered to have chronic hepatitis B. Among HBeAg-negative participants, only 21 (22%) were defined as inactive carriers and 14 (14%) as HBeAg-negative chronic hepatitis B; the majority (61%) had abnormal ALT and low levels of HBV DNA, thus having an indeterminant phenotype. Increasing age was associated with smaller proportions of HBeAg-positive infection. Conclusions: Among children with chronic HBV infection living in North America, the immune tolerant phenotype is uncommon and HBeAg positivity decreases with age. Abstract : Supplemental Digital Content is available in the text